Contextual architecture: a guide to success - Soomro, Ali Raza (2017)
Modern buildings once tended to be conceived as pure, abstract objects, independent of what was beside them mostly added to be sick buildings. As a result became part of energy crisis especially in third world countries. There is now much more attention paid by the contemporary architects to the notion of fitting a building into its existing context to overcome producing further sick buildings. Whereas - trying, in other words, to make certain that the building echoes in its context so far many attempts have been made. However most of the designers are either unaware or consciously have been ignoring the importance of the contextual realities especially by exploiting the advancement of technologies. Through review of history of architecture, case studies and observations an attempt has been suggested as a guide, how to implicate architectural design philosophy in its given context considering the modern technologies and materials. A notion, that if not original at least it may be discreet to be original.